Adsorptive removal of synthetic plastic components bisphenol-A and solvent black-3 dye from single and binary solutions using pristine pinecone biochar. (June 2022) - Gurav, Ranjit; Bhatia, Shashi Kant; Choi, Tae-Rim; Kim, Hyun Joong; Choi, Yong-Keun; Lee, Hong-Ju; Ham, Sion; Cho, Jang Yeon; Kim, Sang Hyun; Lee, Sang Ho; Yun, Jeonghee; Yang, Yung-Hun
Abstract: The existing study deals with adsorptive removal of the endocrine-disrupting chemical bisphenol-A and toxic azo dye solvent black-3 from single and binary solutions. These two chemicals are commonly used as an additive in the synthetic plastic industries. Among the tested twenty pristine and modified biochars, the pristine pinecone biochar produced at 750 °C revealed greater bisphenol-A removal. Simulation of the experimental data obtained for bisphenol-A and dye removal from the single-component solution offered a best-fit to Elovich (R 2 > 0.98) and pseudo-second-order (R 2 > 0.99) kinetic models, respectively. Whereas for the bisphenol-A + dye removal from binary solution, the values for bisphenol-A adsorption were best suited to Elovich (R 2 > 0.98), while pseudo-second-order (R 2 > 0.99) for dye removal. Similarly, the two-compartment model also demonstrated better values (R 2 > 0.92) for bisphenol-A and dye removal from single and binary solutions with greater Ffast values (except for bisphenol-A in binary solution). The Langmuir isotherm model demonstrated the highest regression coefficient values (R 2 > 0.99) for bisphenol-A and dye removal with the highest adsorption capacity of 38.387 mg g −1 and 346.856 mg g −1, correspondingly. Besides, the co-existence of humic acid revealed a positive impact on bisphenol-A removal, while the dye removal rate was slightly hindered in presence of humic acid. The absorption process showed monolayer coverage of biochar surface with contaminants using a chemisorption mechanism with fast reactions between functional groups on the adsorbate and adsorbent. Whereas the adsorption mechanism was primarily controlled by hydrogen bonding, hydrophobic and π-π electron-donor-acceptor interactions as confirmed by FTIR, XPS, and pH investigations. Graphical abstract: Image 1 Highlights: Among twenty tested biochars, pinecone biochar (750 °C) showed higher BPA removal. Pinecone biochar revealed BPA and azo dye removal from single and binary solutions. Elovich and pseudo-second-order were the best-suited models for BPA and dye removal. Co-existence of humic acid enhanced BPA removal, while dye removal rate was impeded. Synthetic plastic components BPA and solvent black-3 dye were significantly removed.